Diseño de actividades con el uso de la visualización para apoyar el proceso de enseñanza aprendizaje de las matemáticas en ciclo IV (2020)
The purpose of this degree work is the design of teaching material for teaching mathematical topics through visualization. It has been made a background study where the leading role is assumed by the development of visualization in teaching mathematical topics.